Development of Chatbot Services for Ordering Media Support Using Fuzzy Logic Algorithm: Case Study of PT. Pemuda Cari Cuan (Mangkokku) - Aris Afriyanto Aris; Yohanes Eka Wibawa (JEECS (Journal of Electrical Engineering and Computer Sciences), 2024)
The importance of customer service in the modern business world cannot be ignored. Providing customers with good service can increase their satisfaction and strengthen the company's and customers' relationship. In the digital era, customer service increasingly shifts to online platforms, such as social media and instant messaging applications. However, providing efficient and responsive services on these platforms can take time and effort. At Mangkokku Restaurant, using social media platforms for promotions, discounts, and other information has become part of the business strategy. However, many customers need help understanding the context of the information in Mangkokku's social media posts. In addition, customers at dine-in outlets often repeat questions about promotions and discounts to the staff at the outlet, especially when the outlet is busy, and the staff needs help providing excellent and fast service. Therefore, research on chatbot services is considered a solution to overcome limitations in communication between staff and customers. With technological advances, chatbots are expected to provide positive benefits. This research uses a fuzzy logic algorithm to help chatbots find the expected response from customers. Apart from that, interviews with the marketing division, customer service, and outlet staff were conducted to collect data on questions and information that needed to be conveyed to customers. In this way, customers at Mangkokku Restaurant are expected to be able to quickly and efficiently ask about menus, promos, discounts, or other information via this chatbot service.